Legal Product Formation and Financial Management - Nirahua, Salmon Eliazer Marthen; Nirahua, Garciano; Soplantila, Ronny (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The village is granted broader authority to regulate and manage the interests of the community. Therefore, a number of village regulations must be created to effectively implement this authority. The importance of these village regulations is also aimed at accelerating the realization of public welfare through improvements in services, empowerment, community participation, and enhancing regional competitiveness, while considering the principles of democracy, equity, justice, as well as the uniqueness and special characteristics of each region within the framework of the Unitary State of the Republic of Indonesia.Purposes of The Devotion: The aim of this community service activity is to enhance the knowledge and skills of the community regarding the position of regional regulations, the process of making regional regulations, and the proper implementation of village governance.Method of The Devotion: Community service is carried out using a legal counseling method that focuses on interactive presentations or seminars, so that the service is not monotonous and does not only rely on the speaker. The topics covered include the formation of regional legal products, or